Communicating Law - as practised by the Danish Tax Authorities, SKAT - Nielsen, Maria Elisabeth (Language at Work - Bridging Theory and Practice, 2007)
How can we write objectively, correctly and understandably when the issue is complicated tax rules, and how can we make the information suit the needs of the end-users? These are some of the questions which the employees of SKAT have to take into consideration before sending letters, brochures and other information material to different enterprises and to the citizens of Denmark.